2007
DOI: 10.1007/s10935-007-0091-y
|View full text |Cite
|
Sign up to set email alerts
|

Closing a Front Door to Homelessness among Veterans

Abstract: The U.S. Department of Veterans Affairs (VA) has been identified as a mainstream institution to help prevent homelessness among America's veterans. The large numbers of incarcerated veterans with serious mental illnesses and substance abuse disorders who are at risk for homelessness support the need for expanded VA outreach to this population. Since 2002, the VA has contacted almost 6,500 veterans in prison or jail. Its leadership role in affording comprehensive health, mental health, social resources, correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Similarly, 38% of VTC participants were receiving VA benefits at program admission which increased to 50% by program exit. Participants with a history of incarceration were less likely to be housed at program exit, supporting previous studies that have pointed to the link between incarceration and homelessness (McGuire 2007; Tsai et al 2014). Additionally, participants who received VA benefits were more likely to be in their own housing at program exit, consistent with studies that have found VA service-connection confers reduced risk for homelessness (Edens et al 2011).…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, 38% of VTC participants were receiving VA benefits at program admission which increased to 50% by program exit. Participants with a history of incarceration were less likely to be housed at program exit, supporting previous studies that have pointed to the link between incarceration and homelessness (McGuire 2007; Tsai et al 2014). Additionally, participants who received VA benefits were more likely to be in their own housing at program exit, consistent with studies that have found VA service-connection confers reduced risk for homelessness (Edens et al 2011).…”
Section: Discussionsupporting
confidence: 85%
“…Previous research has provided two general conclusions about veteran homelessness. First, individual factors associated with homelessness among veterans are very similar to those among nonveterans (Perl, 2015;McGuire, 2007). Among veterans and nonveterans alike, evidence has consistently indicated the prominence of mental illness, substance abuse, and extreme poverty (Balshem et al, 2011;Tsai & Rosenheck, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, among Veterans who are homeless and predominantly justice-involved, rates of multi-morbid physical and mental-health disorders and SUDs have been calculated at 29%; however, only one third of these individuals reported utilizing VA care (M. Cunningham, 2009). Not surprisingly, co-occurring disorders and related circumstances (e.g., homelessness) exacerbate competing basic needs and complicate accessing and engaging in treatment (McGuire, 2007;SAMHSA, 1998). As in the general population, subsections of justice-involved Veterans are likely to require additional care for co-occurring concerns based on demographic factors (e.g., age-related health or psychiatric disorders, reproductive concerns).…”
Section: Co-occurring Disordersmentioning
confidence: 99%